2005
DOI: 10.1182/blood-2004-03-1164
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin dramatically inhibits endothelial cell migration, vascular morphogenesis, and perivascular cell recruitment in vivo

Abstract: IntroductionThe formation of new capillaries from pre-existing vessels (angiogenesis) appears to be essential for tumor growth and survival. [1][2][3][4][5][6] Whereas hypoxic conditions in expanding tumors often initiate a cascade of endothelial cell sprouting and formation of new vessels, tumor growth can be arrested by inadequate blood supply and a lack of metabolic exchange, often leading to tumor necrosis and regression. 7 Several tumor-derived, circulating angiogenesis inhibitors generated in vivo by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…This aspect gains support by an observation that breast cancer patients with elevated endostatin levels following surgery showed a lower risk of relapse (Zhao et al, 2004). Further, a recent publication showed that endostatin dramatically inhibits endothelial cell migration, vascular morphogenesis and perivascular cell recruitment in vivo (Skovseth et al, 2005). These findings underscore the impact of endostatin on endothelial cells in vivo and sustain the hypothesis of a direct relationship between lowered CEC levels and elevated serum endostatin.…”
Section: Discussionsupporting
confidence: 70%
“…This aspect gains support by an observation that breast cancer patients with elevated endostatin levels following surgery showed a lower risk of relapse (Zhao et al, 2004). Further, a recent publication showed that endostatin dramatically inhibits endothelial cell migration, vascular morphogenesis and perivascular cell recruitment in vivo (Skovseth et al, 2005). These findings underscore the impact of endostatin on endothelial cells in vivo and sustain the hypothesis of a direct relationship between lowered CEC levels and elevated serum endostatin.…”
Section: Discussionsupporting
confidence: 70%
“…As an endogenous antiangiogenic protein, ES inhibits endothelial cell proliferation and tube formation (8,9). Since Judah Folkman's laboratory first identified ES (10,11), anticancer effects of ES have been extensively studied in both tumors and tumor-associated endothelia (8,(12)(13)(14).…”
mentioning
confidence: 99%
“…12 The complexity of the ES action mechanism is supported by genome-wide expression profiling studies 13,14 and a recently published work in a surrogate model of human angiogenesis, where ES inhibited EC migration, capillary morphogenesis and perivascular cell recruitment. 15 Given that the combination of antiangiogenic agents with distinct modes of action may result in synergistic effects, 2 we reasoned that a combined therapy with L36 and ES could exhibit greater tumor inhibitory effects than do antibody and ES individually. In this study, we have explored new approaches to combine both activities in one active compound.…”
mentioning
confidence: 99%